Vancomycin-resistant Enterococcus faecium: a national wide genomic snapshot in Switzerland - Dominique S. Blanc; Florian Mauffrey; Andrea C. Büchler; Danielle Vuichard-Gysin; Vanja Piezzi; Céline Gardiol; Marc Garcia; Trestan Pillonel; Laurent Poirel; Patrice Nordmann; Pascal Schlaepfer; Claudio Neidhöfer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Biomarkers of mitochondrial dysfunction and inflammaging in older adults and blood pressure variability - Leonardo Bencivenga; Mathilde Strumia; Yves Rolland; Laurent Martinez; Philippe Cestac; Sophie Guyonnet; Sandrine Andrieu; Angelo Parini; Alexandre Lucas; Bruno Vellas; Philipe De Souto Barreto; Laure Rouch; et al. (GeroScience, 2023)

Limited recovery following a massive seagrass decline in subarctic eastern Canada - Mélanie‐Louise Leblanc; Mary I. O'Connor; Zou Zou A. Kuzyk; Fanny Noisette; Kaleigh E. Davis; Ernie Rabbitskin; Laura‐Lee Sam; Urs Neumeier; Rémi Costanzo; Jens K. Ehn; David Babb; C. Julián Idrobo; et al. (Global Change Biology, 2023)
Over the last few decades, there has been an increasing recognition for seagrasses' contribution to the functioning of nearshore ecosystems and climate change mitigation. Nevertheless, seagrass ecosystems have been deteriorating globally at an accelerating rate during recent decades. In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated in response to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. As part of this research, we compiled and analyzed two decades of eelgrass cover data and three decades of eelgrass monitoring data (biomass and density) to detect changes and assess possible environmental drivers. We detected a major decline in eelgrass condition between 1995 and 1999, which encompassed the entire east coast of James Bay. Surveys conducted in 2019 and 2020 indicated limited changes post‐decline, for example, low eelgrass cover ( 50% cover in eastern James Bay since 1995, representing the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. Using biomass data collected since 1982, but geographically limited to the sector of the coast near the regulated La Grande River, generalized additive modeling revealed eelgrass meadows are affected by local sea surface temperature, early ice breakup, and higher summer freshwater discharge. Our results caution against assuming subarctic seagrass ecosystems have avoided recent global declines or will benefit from ongoing climate warming.

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Stand inventory data from the 10‐ha forest research plot in Uholka: 15 yr of primeval beech forest development - Jonas Stillhard; Martina Hobi; Lisa Hülsmann; Peter Brang; Christian Ginzler; Myroslav Kabal; Jens Nitzsche; Gilbert Projer; Yuriy Shparyk; Brigitte Commarmot (Ecology, 2019)
Forests dominated by European beech ( Fagus sylvatica L.) are among both the most widespread in Europe and the most intensely exploited globally. One of the largest remnants of unmanaged beech forests in Europe is the Uholka‐Shyrokyi Luh forest in Transcarpathia, Ukraine, covering 8,800 ha of primeval forest. In 2000, a permanent forest plot of 10 ha has been established in the Uholka massif. All living and dead trees with a diameter at breast height ( DBH ) ≥ 60 mm were identified to species, DBH measured, stems tagged and mapped. Since then, the plot has been remeasured in 2005, 2010, and 2015. In total, 4,820 individual trees were measured with 14,116 individual measurements throughout all four inventories. In spring 2018, an Airborne Laser Scan was carried out, covering the Uholka‐Shyrokyi Luh forest. This data set allows us to derive a high‐resolution digital elevation model ( DEM ) of the plot area. European beech covers a share of ≈ 95% of the basal area ( BA ) of all living stems. While BA was relatively stable throughout all inventories (≈ 38 m 2 /ha), the number of stems increased considerably between 2010 and 2015 from 290 to 430 stems/ha. Additionally, the proportion of beech stems decreased from 95% in 2010 to 86% in 2015. The continuity of the share of beech on BA and the decrease in number of stems can be traced back to disturbance events, which led to an increase of more light demanding species in the recruitment but did not alter the distribution of BA as these small trees contribute very little to BA . The data set allows for important insights into the development and the spatial and temporal dynamics of primeval beech forests. It can be used to quantify the demographic processes growth, mortality, and recruitment, and to study inter‐ and intraspecific effects on demographic rates, stand structure, and species composition. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

RETRACTED ARTICLE: Omega-3 fatty acid levels in red blood cell membranes and physical decline over 3 years: longitudinal data from the MAPT study - Bertrand Fougère; Sabine Goisser; Christelle Cantet; Gaëlle Soriano; Sophie Guyonnet; Philipe De Souto Barreto; Matteo Cesari; Sandrine Andrieu; Bruno Vellas; Bruno Vellas; Sophie Guyonnet; Isabelle Carrié; et al. (GeroScience, 2017)

BRCA1, BRCA2, TP53, and CDKN2A germline mutations in patients with breast cancer and cutaneous melanoma - Christian Monnerat; Agnès Chompret; Caroline Kannengiesser; Marie-Françoise Avril; Nicolas Janin; Alain Spatz; Jean-Marc Guinebretière; Catalin Marian; Michel Barrois; Françoise Boitier; Gilbert M. Lenoir; Brigitte Bressac-de Paillerets (Familial Cancer, 2007)